"Handbook of industrial statistics, 1987" - India. Ministry of Industry (Delhi, 1987)
This Handbook of Industrial Statistical has been brought out for the first time by the Ministry of Industry with a view to providing in one handy volume diverse statistics on the industrial sector and the economy of the country. It provides time series information on matters such as national income and related macro-economic aggregates, plan outlays and targets, industrial production, public enterprises, investment scenario, employment, technical manpower and R&D foreign trade and trends in prices. A profile of changes in industrial policy has also been included.
Keywords: Industrial statistics